2008
DOI: 10.1007/s00436-008-1145-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of flavonoid compounds from Poncirus trifoliata L. (Family: Rutaceae) against the dengue vector, Aedes aegypti L. (Diptera: Culicidae)

Abstract: The bioactivity of four flavonoid compounds, namely poncirin, rhoifolin, naringin and marmesin, from Poncirus trifoliata was studied against the Aedes aegypti. Larvicidal assays were conducted to evaluate the 24 h LC(50) and LC(90) values of the flavonoid compounds. The lethal concentration (LC(50) and LC(90)) values ranged from 0.082 to 0.122 mg/l and 0.152 to 0.223 mg/l, respectively. The result of ovicidal test suggests that the ovicidal activity of the flavonoid compounds was influenced by the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Several reports are available regarding the repellent properties of essential oils against adult mosquitoes [18][19][20] ; however very few works have been reported proving the irritability potential of leaf extracts and practically no work with Citrus leaf extracts. Our studies showed the significant irritancy potential of hexane extracts of Citrus leaves against the adults of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports are available regarding the repellent properties of essential oils against adult mosquitoes [18][19][20] ; however very few works have been reported proving the irritability potential of leaf extracts and practically no work with Citrus leaf extracts. Our studies showed the significant irritancy potential of hexane extracts of Citrus leaves against the adults of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Zebitz (1984Zebitz ( , 1986 reported that the A. indica seed kernel extract showed ovicidal and oviposition deterrent against A. aegypti, and Mohsen et al (1995) reported similar activity against A. albopictus. Rajkumar and Jebanesan (2008) reported that the isolated compounds from Ponicrus trifoliata showed remarkable ovicidal and oviposition deterrent activity against A. aegypti. The effect on nontarget organisms revealed that PON-NEEM was harmless to predatory fish G. affinis and predatory insect D. indicus.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical survey of this family reveals alkaloids, coumarins, flavonoids, limonoids, and volatile oils [4]. Many of these compounds have been associated to different biological activities, for example, antimicrobial [3,5], antidiarrhoeal [6], anticholinesterasic [7], antileishmanial [8], antiprotozoal [9], larvicidal [10,11], and antioxidant activities [12,13]. In family Rutaceae, the genus Zanthoxylum has been able to provide a variety of secondary metabolites with interesting phytochemical and biological activities [14].…”
Section: Introductionmentioning
confidence: 99%